Analysis and Assessment of Wind Energy Potential of Almukalla in Yemen - Almekhlafi, Murad A. A.; Al-Wesabi, Fahd N.; Eltahir, Majdy M.; Hilal, Anwer Mustafa; El-Kustaban, Amin M.; Motwakel, Abdelwahed; Yaseen, Ishfaq; Hamza, Manar Ahmed (Tech Science Press, 2022)
This study analyzed and assessed the wind energy potential of Almukalla, Yemen by evaluating wind characteristics, available power density, and extractable wind energy at different heights. The study used wind data to estimate the technical potential of wind energy in the study area and to support renewable energy planning.